Processamento de folhas de nim: inativação enzimática e secagem - Parckert, Evely Degraf Terra (2009)
The purpose of the present study was to develop a Neem (Azadirachta indica) leaves processing technology an enzymatic inactivator (fast pre-heating device, sapecador ) as a pilot project following by drying process in a tray dryer with heating air. The best operational condition consisted on fast pre-heating ( sapeco ) for 5 min running the device in 200.1 rpm. The final product resulted in olive green coloration, brittle aspect and absence of peroxidase enzyme. The initial moisture of leaves was reduced from 88.33% (wet base) to 24.81% (wb) after 5 min of fast pre-heating process ( sapeco ). Using a try drier with hot air stream (60ºC) at 0.55 m/s. After 120 min of drying process the leaves moisture content, in wet base, was 5% approximately, that is an appropriate value for storage. After grinding of dried leaves, 80.45% of particles has size less than 0.149 mm (100 mesh Tyler). In the moisture content of 5.86%, in wet base, superficial contraction of 19.6% on leaf surface has occurred.